Exploring the potential of palm oil plantation waste for local communities using mixed methods - A. Ilhami; T. Hidayat; Riandi . (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Riau is Indonesia's largest palm oil supplier region, part of which is managed by smallholder farmers. The escalation in the worldwide need for palm oil has resulted in the expansion of plantations, consequently causing a rise in palm oil waste. Small-scale farmers lack sufficient knowledge and resources for waste management. The study seeks to estimate and forecast the volume of palm oil waste generated and the utilization inventory by indigenous populations in Riau province.METHODS: The present study employs a combination of quantitative and qualitative methodologies. Utilizing secondary data obtained from the Central Statistics Agency, the research calculates the volume of waste generated by smallholder oil palm plantations and forecasts the quantity of palm oil waste. The prediction method uses the time series modeler method with the help of a statistical package for the social sciences 23. Subsequently, surveys were employed to gather quantitative information regarding the utilization of palm oil waste by indigenous populations in the province of Riau. The respondents involved were 112 people using the convenience sampling method. Descriptive statistics are utilized in data analysis to determine the quantity of waste and to gain insight into the local population's utilization. Interviews were also conducted with seven local people who work as farmers regarding the management and use of palm oil waste. Interview data were analyzed using descriptive qualitative methods.FINDINGS: Analysis of smallholder plantation waste in Riau shows that the most significant type is stem parts at 82 percent. Palm oil waste will increase to 236.37 million tons in the next decade. Approximately 80 percent of local communities handle plantation waste by depositing it on plantations for natural decomposition.CONCLUSION: The amount of smallholder plantation waste is enormous and will continue to increase. It is crucial to prioritize the improvement of waste management standards at the local community level in order to promote the sustainability of palm oil plantations. The findings significantly contribute to promoting sustainable environmental management, providing actionable insights for policymakers and environmental activists.